2003
DOI: 10.1093/mutage/18.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of DNA-protein crosslinks and micronuclei in peripheral lymphocytes of tannery workers exposed to trivalent chromium

Abstract: DNA-protein crosslinks (DPC) are a promising biomarker of exposure to hexavalent chromium, a known human carcinogen. Although trivalent chromium is considered to have much lower toxicity, the risk involved in chronic exposure is uncertain. DPC may be a useful tool in clarifying this risk, by signaling an exposure of body tissues to biologically active forms of chromium. DPC quantification was carried out in lymphocytes of a group of tannery workers exposed to trivalent chromium, a small group of manual metal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 43 publications
7
46
1
1
Order By: Relevance
“…Chromium was reported to be a genotoxic carcinogen affecting the fragile site, a heritable point on the chromosome where gaps and breaks tend to occur. The results obtained in this study might be strongly supported by the detectable increase in lymphocyte DNA damage due to chronic occupational exposure to Cr-III which correlated significantly with exposure of the cells to the metal [36] . Although the precise mechanisms remain to be elucidated, there is evidence for a role of oxidative DNA damage in the genotoxicity [8] .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Chromium was reported to be a genotoxic carcinogen affecting the fragile site, a heritable point on the chromosome where gaps and breaks tend to occur. The results obtained in this study might be strongly supported by the detectable increase in lymphocyte DNA damage due to chronic occupational exposure to Cr-III which correlated significantly with exposure of the cells to the metal [36] . Although the precise mechanisms remain to be elucidated, there is evidence for a role of oxidative DNA damage in the genotoxicity [8] .…”
Section: Discussionsupporting
confidence: 74%
“…However, in another study, no significant difference was observed between exposed and controls workers exposed to chromium with regard to the frequency of peripheral lymphocytes with chromosome aberrations [35] . Nowadays, DNA-protein cross-links are considered a promising biomarker signaling an exposure of body tissues to biologically active forms of chromium [36] .…”
Section: Discussionmentioning
confidence: 99%
“…The fumes from industrial stainless steel welding processes also increased CA in 11 welders [Borska et al, 2003]. As part of a large study on tannery workers, Medeiros et al [2003] reported that five welders had a higher frequency of DNA-protein crosslinks than the control group. However, probably due to the small number of welders involved in this study, the authors reported no increase in the frequency of micronuclei for these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, biological endpoints, such as DNA damage, can be monitored by analysis of CA and SCE [Jelmert et al, 1995], micronuclei in either buccal cells [Danadevi et al, 2004] or lymphocytes [Medeiros et al, 2003], DNA-protein crosslinks [Costa et al, 1993], or unscheduled DNA synthesis [Knudsen et al, 1992]. In addition, the alkaline Comet assay is a rapid and sensitive technique to assess DNA strand breaks and alkali-labile sites in individual cells.…”
Section: Introductionmentioning
confidence: 99%
“…Of importance from a practical standpoint, SCEs appear to result only as an effect of chemical mutagens, not radiation. They are most efficiently induced by substances that form covalent adducts to the DNA, distort the DNA helix, or interfere with DNA precursor metabolism or repair (Medeiros et al, 2003).…”
Section: Sister Chromatid Exchangementioning
confidence: 99%